Experimental Identification of the Dynamic Characteristics of a Flexible Rocking Structure. Issue 8 (16th November 2016) - Acikgoz, Sinan; Ma, Quincy; Palermo, Alessandro; DeJong, Matthew J.
Abstract : This article presents the results of free vibration and earthquake excitation tests to investigate the dynamic behavior of freely rocking flexible structures with different geometric and vibration characteristics. The primary objective of these tests was to identify the complex interaction of elasticity and rocking and discuss its salient effects on the rocking and vibration mode frequencies, shapes and excitation mechanisms. The variability of response is discussed, including critical investigation of the repeatability of the tests. It was found that the variability in energy dissipation and energy transfer to vibrations at impact may lead to significantly different responses to almost identical excitations.